KOMUNIKASI POLITIK DAN DIPLOMASI BERBASIS KEARIFAN LOKAL DALAM MASA KAMPANYE PEMILUKADA KABUPATEN KUANTAN SINGINGI TAHUN 2011 - Ridwan, Mumammad (Universitas Riau, 2013)
Political communication is important and feels more important when we listen to and browse thefunctions of political communication itself , especially when political communication and politicaldiplomacy based on local wisdom . Political communication is done to promote the politicaldesires of Regents candidates Singingi Kuantan , poor judgment in taking the values of localwisdom which contains many morals , truth values , family values and religious values can not beblocked causing conflicts terjaddi The Regency Kuantan Singingi Election in 2011 . One exampleof local wisdom kuantan singing the